La armonización en el Espacio Europeo de Educación Superior: El estado de la cuestión / Harmonization in the European higher education: State of the question - Feisal Cárdenas, John (Journal of Supranational Policies of Education (JOSPOE), 2016)
ABSTRACT This paper presents a comparative analysis of the current landscape of the new European Higher Education Area in the European Union with regard to the achievement of a real harmonization of the education systems of higher education in the countries that comprise it. In light of the proposed harmonization of Higher Education in the European Union, having as starting point the Sorbonne Declaration. Joint declaration on harmonization of the design of the European Higher Education System in 1988, is intended to analyze the actual state of the European harmonization of Higher Education, through the knowledge of national educational structures of the academic level and implementation in a number of selected countries. Key words: Higher Education, European Higher Education Area, Harmonization, European Union, Bologna Process. RESUMEN Este trabajo presenta un análisis comparado del panorama actual del nuevo Espacio Europeo de Educación Superior de la Unión Europea en lo referido a la consecución de una armonización real de los sistemas educativos de Educación Superior de los países que lo conforman. A la luz de las propuestas de armonización de la Educación Superior en la Unión Europea, que tienen como punto de partida la Declaración de la Sorbona. Declaración conjunta para la armonización del diseño del Sistema de Educación Superior Europeo en el año 1988, se pretende realizar un análisis del estado real de dicha armonización de la Educación Superior Europea, a través del conocimiento de las estructuras educativas nacionales de este nivel académico y su implantación en una serie de países escogidos. Palabras clave: Educación Superior, Espacio Europeo de Educación Superior, Armonización, Unión Europea, Proceso Bolonia.